2020
DOI: 10.9734/jamcs/2020/v35i230252
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of COVID-19 Transmission in Kenya Using Compound Poisson Regression Model

Abstract: Since the inception of the novel Corona Virus Disease-19 in December in China, the spread has been massive leading World Health Organization to declare it a world pandemic. While epicenter of COVID-19 was Wuhan city in China mainland, Italy has been affected most due to the high number of recorded deaths as at 21st April, 2020 at the same time USA recording the highest number of virus reported cases. In addition, the spread has been experienced in many developing African countries including Kenya. The Kenyan g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Relationships between yield losses and damages caused by pests can be well expressed using regression statistics [8,9]. Generalized linear regression models have been shown to be effective and reliable for detecting relationships between parameters [11] and are widely acceptable. The linear regression models generated by this study are highly reliable, as their coefficients of determination (R 2 ) were mostly significant (P ≤ 0.05) and largely close or > 50 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between yield losses and damages caused by pests can be well expressed using regression statistics [8,9]. Generalized linear regression models have been shown to be effective and reliable for detecting relationships between parameters [11] and are widely acceptable. The linear regression models generated by this study are highly reliable, as their coefficients of determination (R 2 ) were mostly significant (P ≤ 0.05) and largely close or > 50 %.…”
Section: Resultsmentioning
confidence: 99%
“…Since crop pests are inherently part of every agroecosystem, estimating their contributions to crop performance is very important [10], and this area of investigation is currently receiving high attention in the field of pest management. The use of generalized linear regression has been shown to be proper and is widely acceptable in detecting the relationships between factors [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the multivariate analysis, the contact persons and flights to Kenya had 0.278 and 3,309 effects on COVID-19 cases in Kenya at the 5% and 10% levels of significance, respectively. Researchers in Kenya also used the compound Poisson regression model, which showed that as the COVID-19 day increased by 235, the COVID-19 new cases were projected to 83,418 new cases [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the week 4 death counts significantly predicted the week 5 death count. And, there was a correlation between COVID-19 new cases and contact persons with confirmed status as well as the number of flights from foreign countries to Kenya (Anwar et al 2020;Ghosal et al 2020;Odhiambo et al 2020;Montalban et al 2020;Tadle et al 2020;Yonar 2020).…”
Section: Literature Reviewsmentioning
confidence: 99%